PENERAPAN METODE HERBATH DALAM PEMBELAJARAN QAWAID BAHASA ARAB DI SMP PLUS SUNAN AMPEL NGRONGGO KOTA KEDIRI: Penerapan metode Herbath dalam pembelajaran Qawaid bahasa Arab , Kendala-kendala penerapan metode Herbath dalam pembelajaran Qawaid bahasa Arab, Manfaat penerapan metode Herbath dalam pembelajaran Qawaid bahasa Arab - nafis wasi'un nadhory; Ahmad Rifa'i (Institut Agama Islam Negeri Pontianak, 2025)
Effective and well directed Qawaid learning in Arabic language naturally requires a suitable and supportive teaching method. One such method that can be utilized is the Herbath method. This method consists of five systematic steps, namely preparation, presentation, association, generalization and application. This study aims to describe the implementation of the Herbath method ini teaching Arabic Qawaid at SMP PLUS Sunan Ampel. The research employs a qualitative descriptive approach with data collection teahniques including observation and interviews, the object of the research ist the implementation of the Herbath method in Arabic Qawaid learning, while the subjecst are the Arabic language teacher of grade VIII and the grade VIII students who take Arabic classes. The results of the study show that the implementation of the Herbath method in Arabic Qawaid instruction is carried out in a gradual and systematic manner. However, there are several challenges encountered during its application, such as limited time, lack of student participation, the burden of memorization and minimal use of learning media. Despite these obstacles, implementation of the Herbath method in Qawaid learning offers several benefits in each of its stages. These include enhancing students’ understanding of various grammatical rules, enabling them to construct correct sentences and helping them align vocabulary with proper grammatical structures